The Impoliteness Strategies Found in Ron Clark Story Movie - Yaningsih, Tri; , Agus Wijayanto, Ph.D; , Mauly Halwat Hikmat, Ph. D. (2015)
ABSTRACT TRI YANINGSIH. S200120052. 2015. The Impoliteness Strategies Found in Ron Clark Story Movie. Thesis.Magister of Language Study.Faculty of Language Department.Muhammadiyah University of Surakarta. This research aims at: (1) describing the impoliteness strategies. (2) describing the gender on impoliteness. (3) describing the social position on impoliteness, and (4) describing the social distance on impoliteness in Ron Clark Story movie. The type of research is qualitative method. The qualitative research is carried out by making use of the descriptive method. The object of the research is the impoliteness in Ron Clark Story movie. The data are the utterances involving impoliteness. The writer analyzes the data by using Culpeper's impoliteness theory and sociology approach. The approaches are used for analyzing the impoliteness, the genders, the social positions, and the social distances in involving impoliteness. Based on the result of the data analysis, the writer finds some impoliteness strategies, gender involves impoliteness, social position involves impoliteness, and social distance involves impoliteness. The data were collected using documentation. There are four kinds of impoliteness strategies used. They are Bald on Record Impoliteness, Positive Impoliteness, Negative Impoliteness, and Withhold Politeness. From the four impoliteness strategies is dominated by the positive impoliteness strategy. There is no difference between male and female in performing impoliteness strategy. All of the genders perform impoliteness. The utterances from male are direct, forceful, and unmitigated. But the writer found the utterance from female characters in Ron Clark Story movie is the same with the utterance from the male characters. The impoliteness is not merely from higher to lower social position. In Ron Clark Story movie, the writer finds that the data are dominated by impoliteness from lower to higher social position. All of the social distances involve impoliteness. The data are led by impoliteness from the characters in less familiar social distance. As a teacher, the writer hopes that the result of this research will be useful to educate her students not to involve impoliteness. Key words: Impoliteness, Ron Clark Story, Gender, Social Position, Social Distance.